2020
DOI: 10.5860/crl.81.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Initiatives to Recruit and Retain Academic Librarians: A Systematic Review

Abstract: Libraries across Canada and United States are adopting diversity initiatives to encourage inclusive library environments and services. Many policies and frameworks have a user-centered approach. However, there is little focus on encouraging diverse service providers in the library. The aim of this study is to determine the strategic approaches that academic libraries are using in their efforts to recruit and retain diverse librarians. Systematic review methodology involved searching Library & Information Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 9 publications
(11 reference statements)
1
17
0
Order By: Relevance
“…have contributed to a state of affairs that degrades nonwhiteness by commodifying it and that relegates nonwhite individuals to the status of 'trophies' or 'passive emblems'" (p. 2156). It is important to address these issues as diversity, equity and inclusion statements and initiatives have increased significantly in Canadian and US academic libraries (Kung et al, 2020). Though these statements are important, more action is needed in dismantling racist and exclusionary practices and structures that have been rendered invisible.…”
Section: A Discussion On Racial Capitalism and Libraries 127mentioning
confidence: 99%
“…have contributed to a state of affairs that degrades nonwhiteness by commodifying it and that relegates nonwhite individuals to the status of 'trophies' or 'passive emblems'" (p. 2156). It is important to address these issues as diversity, equity and inclusion statements and initiatives have increased significantly in Canadian and US academic libraries (Kung et al, 2020). Though these statements are important, more action is needed in dismantling racist and exclusionary practices and structures that have been rendered invisible.…”
Section: A Discussion On Racial Capitalism and Libraries 127mentioning
confidence: 99%
“…54 However, recruiting and hiring diverse staff is challenging as the number of visible minorities in academic librarianship has remained stagnant. 55 Retaining academic librarians and staff of color is a separate challenge, as institutional and library environments, expectations and research output are all explicit barriers, while internal pressure and time management constraints are implicit barriers. 56 Academic librarians and staff of color are subject to racial microaggressions perpetrated by unaware nonminority colleagues, an issue that permeates higher education, particularly at historically white institutions (HWIs).…”
Section: Orientational Implications Of Dei Statementsmentioning
confidence: 99%
“…However, these types of professional standards and programs have not led to substantive changes within academic libraries or librarianship. A recent systematic review found that while broader diversity initiatives aimed at creating inclusive library services are fairly common, research libraries have routinely failed to make meaningful progress in recruiting and retaining staff members from historically underrepresented minorities: "the number of visible minorities in the field has remained stagnant for decades" (Kung et al 2020). While some institutions may hope to address these trends by including items such as diversity statements or expressing commitment to Equal Employment Opportunity/Affirmation Action within PPDs, including specific qualifications related to DEI within PPDs may be a more effective way of advancing institutional DEI by highlighting that successful incumbents will be evaluated in these areas.…”
Section: Required and Preferred Qualificationsmentioning
confidence: 99%